(untitled) (Eurasian Journal of Religious Studies, 2016)
In the article recommendations are mine-out on the prophylaxis of terrorism and extremism among young people. And also the questions of fight are examined against influence of destructive religious associations. In the modern world where, the role of socio-economic, political and cultural mutual relations increases religious extremism became one of the discussed themes of political figures and religious leaders. One of the most dangerous factors of further development of civilization is a height of religious extremism and terrorism. The modern global world compels us to be vigilant and to undertake the certain operating under the examined question in advance in fact a social evil it is easy to prevent, than to reap his garden-stuffs. It is possible to say with a confidence, that presently a most threat for society is presented not simply by extremism, and religious extremism and terrorism. His distinguishing feature is in that he is sent to the violent change of the political system and capture of power, violation.